The effectiveness of a MOOC in basic mathematics and time management training for transfer students in engineering. (3rd July 2020) - Van den Broeck, Lynn; De Laet, Tinne; Lacante, Marlies; Pinxten, Maarten; Van Soom, Carolien; Langie, Greet
ABSTRACT: When students enter higher education, they can encounter the feeling of unpreparedness. In fact, students who lack the appropriate prior education are less prepared. Therefore developing and implementing appropriate interventions for incoming students is important. This study examined the effectiveness of two new interventions at the Faculty of Engineering Technology, KU Leuven: (1) a basic mathematics MOOC and (2) a time management training. Transfer students were given the opportunity to participate voluntarily. Some preliminary empirical evidence about the effectiveness of the interventions was found, based on analysis of pre- and post-test scores, a satisfaction survey, and a math diagnostic test. This study found statistical evidence for the effectiveness of the math MOOC. Regarding the effectiveness of the time management training, the evidence was marginally non-significant. However, students who participated in the time management training perceived the training as useful. Therefore, we keep organising this training, which focuses on a non-cognitive variable.